Mastocytosis in the age of precision medicine: Position paper of the German Society of Allergy (AeDA) on the management of indolent systemic mastocytosis - Siebenhaar, Frank; Brehler, Randolf; Christen, Deborah; Hartmann, Karin; Altrichter, Sabine; Joest, Marcus; aufm Kampe, Kristin; Lang, Claudia C.V.; Lippert, Undine; Mülleneisen, Norbert; Ott, Hagen; Panse, Jens; et al. (Allergo Journal, 2025)
Mastocytosis encompasses a spectrum of clonal mast cell disorders characterized by the proliferation and accumulation of atypical mast cells in various organs, including the skin, bone marrow, and gastrointestinal tract. Initially described in 1869 as a cutaneous manifestation, the systemic variant (SM), involving additional organs, was documented in 1949. Clinical distinctions are made between indolent SM (ISM), where mediator-related symptoms predominate, and more aggressive forms, in which organ dysfunction is the primary concern. In recent decades, there has been continuous progress in elucidating the pathogenesis, classification, and management of mastocytosis, aided by specialized networks such as the European Competence Network Mastocytosis (ECNM) and the German Competence Network on Mastocytosis (Kompetenznetzwerk Mastozytose e. V.). A significant therapeutic advancement has been the development of targeted tyrosine kinase inhibitors, including midostaurin and avapritinib, which have been utilized for several years in treating aggressive SM. Recently, avapritinib in lower dosage was also approved for ISM patients with moderate to severe symptoms. For patients with milder forms of ISM, a symptom-oriented basic therapy is recommended. The diagnosis of SM requires interdisciplinary collaboration and strict adherence to established diagnostic criteria. Moreover, innovative patient-centered approaches, such as the MASTHAVE® app, support ongoing follow-up and have the potential to enhance quality of life. Long-term research efforts are increasingly directed toward developing personalized therapies that target the molecular mechanisms underlying the disease.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Mast cell disease; Mast cells; Mastocytosis; Personalized medicine; Tyrosin kinase inhibitors